Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells

Organic-inorganic perovskitoid with zwitterion cysteamine linker and its crystal-crystal transformation to ruddlesden-popper phase - Kour, Prachi; Reddy, Mallu Chenna; Pal, Shiv; Sidhik, Siraj; Das, Tisita; Pandey, Padmini; Mukherjee, Shatabdi Porel; Chakraborty, Sudip; Mohite, Aditya D.; Ogale, Satishchandra (Angewandte Chemie-International Edition, 2021)
We demonstrate synthesis of a new low-D hybrid perovskitoid (a perovskite-like hybrid halide structure, yellow crystals, P21/n space group) using zwitterion cysteamine (2-aminoethanethiol) linker, and its remarkable molecular diffusion-controlled crystal-to-crystal transformation to Ruddlesden-Popper phase (Red crystals, Pnma space group). Our stable intermediate perovskitoid distinctly differs from all previous reports by way of a unique staggered arrangement of holes in the puckered 2D configuration with a face-sharing connection between the corrugated-1D double chains. The PL intensity for the yellow phase is 5 orders higher as compared to the red phase and the corresponding average lifetime is also fairly long (143 ns). First principles DFT calculations conform very well with the experimental band gap data. We demonstrate applicability of the new perovskitoid yellow phase as an excellent active layer in a self-powered photodetector and for selective detection of Ni2+ via On-Off-On photoluminescence (PL) based on its composite with few-layer black phosphorous.
Keywords: Crystal growth; organic-inorganic hybrid composites; perovskite phases; photodetectors; zwitterions